Knowledge, attitudes and practices towards breastfeeding among mothers in Tumpat, Kelantan - Azahar, Amira Syazreen (Universiti Sains Malaysia, 2015)
Breastfeeding has been actively promoted in Malaysia in the last few years in all public and private hospital. In Malaysia, the National Breastfeeding Policy was formulated in 1993 whereby exclusive breastfeeding was recommended for the first four to six months of life and continued up to two years. The prevalence of exclusive breastfeeding among children below six months was low about 15% in Malaysia. Thus, the current breastfeeding patterns are still far from the recommended levels. Compared to other countries in the Southeast Asian region, Malaysia is the country with the lowest prevalence of exclusive breastfeeding. This study proposed to find out knowledge, attitude and practice towards breastfeeding among mothers in kampung Baru Nelayan, Tumpat, Kelantan. The questionnaire consist of three parts and descriptive statistic were used to organize and summarize the information obtained from a sample (n= 110) of the population. The results from the KAP study shown that the prevalence of exclusive breastfeeding and complementary breastfeeding was 55% respectively. Apart from that, the results indicate most mother are shy to breastfeed in public and they were more likely to breastfeed in public if there is a suitable placed. Mothers with a positive attitude on breastfeeding and those who possess a secondary educational level were associated with longer duration of breastfeeding. Spouse and family members played an important role in building up a mother’s confidence to breastfeed her child. Mothers preferences are important in the decision to initiate breastfeeding and continue exclusive breastfeeding for the recommended 6 months minimum.